The effect of direct instruction and interactive instructional videos on learning effectiveness and ef-ficiency in mathematics education - Andreas M. Zendler (Universitas Sembilanbelas November Kolaka, 2020)
This study focuses on the empirical examination of learning effectiveness and efficiency concerning two instructional methods: Direct instruction and interactive instructional videos. An SPF-2×2•2 design is used to control the instructional method, lessons, and class context. Learning outcome on probability calculation is assessed about effectiveness (grade) and efficiency (time required). The empirical findings show that learning with interactive instructional videos performs well regarding direct instruction. This is a significant result in the digitization of instructional methods.